Gene Expression Analysis using Markov Chains extracted from Recurrent Neural Networks - Almeida, Ígor Lorenzato; Pechmann, Denise Regina; Amarante, Maicon de Brito do; Cechin, Adelmo Luis (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2009: Anais do VII Encontro Nacional de Inteligência Artificial, 2009)
This paper presents a new approach for the analysis of microarray data by the use of Recurrent Neural Networks (RNNs) as a time model of the gene regulatory network. Our method extracts a Markov Chain (MC) from a trained RNN and the relations among genes in each MC state. We propose to use the learning ability of RNNs for the automatic construction of the model with the gene interactions represented by the weights and afterwards to use an algorithm to extract these relations in the form of MCs and linear matrices easily visualized in the form of graphs of states and genes. The graph of states show the evolution of the gene expression levels in time while the gene graph shows the dependencies among genes in each Markov state.